VR Application to Teach Ergonomics Knowledge to Offshore Worker (OngTech) - Wong, Li Ong (IRC, 2019)
Nowadays, Virtual Reality (VR) is one of the hottest technology trends. Although gaming is probably the most popular commercial application of VR at current trend, VR has also found fast and deep adoption in the fields of training and education. Some of the school or companies had gave training and teaching through VR so that trainee can understand better and experience it in a virtual world instead of listening only. There is a very critical problem which is many accidents occurred to offshore workers during working and the accidents happened are usually due to lack of knowledge and training among the workers. Hence, the purpose of this project is to develop a VR application called OngTech to provide the training to offshore workers about the drilling ergonomics. The result of OngTech can provide the knowledge about drilling ergonomics to offshore workers in order to reduce the happening of accidents at offshore workplace. For the development, Unity software was used as a platform to develop the system by using C# script and the methodology for this project is Rapid Application Development (RAD).